Race: The Difference That Makes a Difference - Syed Mustafa Ali (tripleC: Communication, Capitalism & Critique)
During the last two decades, critical enquiry into the nature of race has begun to enter the philosophical main-stream. The same period has also witnessed the emergence of an increasingly visible discourse about the nature of infor-mation within a diverse range of popular and academic settings. What is yet to emerge, however, is engagement at the interface of the two disciplines – critical race theory and the philosophy of information. In this paper, I shall attempt to con-tribute towards the emergence of such a field of enquiry by using a reflexive hermeneutic (or interpretative) approach to analyze the concept of race from an information-theoretical perspective, while reflexively analyzing the concept of informa-tion from a critical race-theoretical perspective. In order to facilitate a more concrete enquiry, the concept of information formulated by cyberneticist Gregory Bateson and the concept of race formulated by philosopher Charles W Mills will be placed at the centre of analysis. Crucially, both concepts can be shown to have a connection to the critical philosophy of Immanuel Kant, thereby justifying their selection as topics of examination on critical reflexive hermeneutic grounds.